Pengaruh Kualitas Produk dan Promosi terhadap Kepuasan Nasabah pada Lembaga Perkreditan Desa (LPD) Desa Pakraman Padangsambian - SANJAYA, I GUSTI NGURAH OKA; BUDIASA, I WAYAN; DEWI, NI LUH PRIMA KEMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Effect of Product Quality and Promotion on Customer Satisfaction at the Village Credit Institution (LPD) of Pakraman Padangsambian Village.  The process of economic globalization has influenced the growth and development of the financial services sector in Indonesia. One that has a role in the financial services sector is financial institutions. This makes it a challenge for a company to have superior products and maintain the quality of its products. The efforts made by the company are to promote the products offered. This study aims to determine the effect of product quality and promotion on customer satisfaction at the Village Credit Institution (LPD) of Pakraman Padangsambian Village. The sample determination technique uses purposive sampling. The sample determination used the Slovin formula so that 45 respondents were taken. This study used descriptive statistics and inferential statistics. The analysis tool is modeled into the SEM-PLS model with the help of SmartPLS v 3.2.9 software. The results showed that the product quality has an original sample value of 0.510 and a p-value of 0.000, so that product quality has a positive and significant influence on customer satisfaction. In addition, the results showed that promotion has an original sample value of 0.406 and a p-value of 0.002, so that promotion has a positive and significant influence on customer satisfaction. This research suggestion is for LPD Pakraman Padangsambian Village to create new products, such as providing Unsecured Credit (KTA) products given to customers for social activities. In addition, in order to carry out product promotion activities in the form of advertisements or distribution of brochures.